Retrospective parent report of early vocal behaviours in children with suspected Childhood Apraxia of Speech (sCAS) - Highman, Chantelle; Hennessey, Neville; Sherwood, M.; Leitao, Susan (Sage Publications, 2008)
Parents of children with suspected Childhood Apraxia of Speech (sCAS, n = 20), Specific Language Impairment (SLI, n = 20), and typically developing speech and language skills (TD, n = 20) participated in this study, which aimed to quantify and compare reports of early vocal development. Via a questionnaire, parents reported on their child's early babbling and vocalizations, along with other developmental milestones. Consistent with previous anecdotal reports and theoretical predictions, the sCAS children were reported to be significantly less vocal, less likely to babble, later in the emergence of first words and later in the emergence of two-word combinations than the TD children. However, on many (but not all) of the items, the SLI children were reported similarly to the sCAS group. Notable exceptions where the sCAS group differed significantly to the SLI group were with the percentage of children reported to have babbled and the reported age of emergence of two-word combinations. The results support previous anecdotal clinical suggestions relating to children with CAS but highlight the need for longitudinal studies to analyse speech and language trajectories over time.